Physical Properties of Materials - White, Mary Anne (Boca : Raton CRC Press, 2012)
Physical Properties of Materials, Second Edition establishes the principles that control the optical, thermal, electronic, magnetic, and mechanical properties of materials. Using an atomic and molecular approach, this introduction to materials science offers students a wide-ranging survey of the field and a basis to understand future materials. The author incorporates comments on applications of materials science, extensive references to the contemporary and classic literature, and problems at the end of each chapter. In addition, unique tutorials allow students to apply the principles to understand applications, such as photocopying, magnetic devices, fiber optics, and more.This fully revised and updated second edition presents a discussion of materials sustainability, a description of crystalline structures, and discussion of current and recent developments, including graphene, carbon nanotubes, nanocomposites, magnetocaloric effect, and spintronics. Along with a new capstone tutorial on the materials science of cymbals, this edition contains more than 60 new end-of-chapter problems, bringing the total to 300 problems.
Includes bibliographical references; Index 437-452p.
Keywords: Physical properties of material; Physics